Tuberculosis infection control in selected facilities managing drug-resistant tuberculosis in Bangladesh: Findings from a mixed-methods study - Parray, A.A. (Elsevier, 2022)
This article was published in the International Journal of Infectious Diseases by Elsevier [© 2020 Published by Elsevier Inc.] and the definite version is available at: https://doi.org/10.1016/j.ijid.2020.09.797 The Journal's website is at: https://www.sciencedirect.com/science/article/pii/S1201971220315137